Surgery performed for chronic otitis media at Chris Hani Baragwanath Academic Hospital: an 18-month retrospective clinical audit - Joubert, Wynand (My University, 2013)
The surgical management of chronic otitis media is ever evolving. This is also the case at the Chris Hani Baragwanath Academic Hospital where in recent times, certain new techniques were adopted and other older ones revisited. This changed surgical approach was deemed to be necessary not only in view of the limited resources available to deal with a large patient load, but also to improve surgical outcomes in the local environment. The focus was mainly on the implementation of internationally accepted surgical techniques that have been shown to not only be effective and safe, but also simple and time-saving. Changes were mostly seen in the management of patients presenting with simple perforations and cholesteatoma. It is the objective of this study to formally assess the outcome and feasibility of this changed surgical approach, as well as to assess the outcomes of surgery as a whole. A retrospective clinical chart review was undertaken over an eighteen-month period from July 2009 to December 2010. All patients undergoing single stage surgery for chronic otitis media in this period were included, and grouped in terms of procedure performed, viz. Tympanoplasty, Tympanomastoidectomy and Canal wall down CWD mastoidectomy. All data were collected from an otological database, each case independently evaluated in terms of surgical and audiological outcomes after at least a 2 month follow up period. Only data acquired at the latest follow-up date were used. The follow up period ranged from 2 to 18 months. The Butterfly Cartilage Inlay Graft (BCIG) tympanoplasty technique was the predominant technique used for simple perforations of any size and location, and showed superior surgical outcomes to the more traditional Fascia underlay graft (FUG) technique. Surgical success (i.e. healed / intact tympanic membrane) in the FUG tympanoplasty group was 75%, compared to 93% in the BCIG group. One hundred percent of cases subjected to BCIG tympanoplasty achieved sociable hearing (ACT< 30dB) in the early post-operative period. We found the hearing improvement post-surgery to be directly related to the size of perforation (p= 0, 0195), and pre-operative hearing loss (p= 0, 0001 r= 0.93). None of the other variables studied influenced the audiological outcome achieved. In the study period, surgical techniques used for more severe Noncholesteatomatous chronic otitis media (NCCOM) were little changed from before. An evaluation of these cases focused on those with actively discharging ears to assess the outcome of Tympanomastoidectomy to achieve not only a dry ear, but also an intact tympanic membrane (TM) and hearing improvement (HI). Eighty-six percent of patients with discharging ears had dry ears post-operatively, 50% of which achieved an intact tympanic membrane and sociable hearing (ACT< 30dB). Graft failures in the tympanomastoidectomy group as a whole were mostly related to size of perforation (p= 0,047) and to the presence of discharge pre-operatively (p= 0,012). In the CWD mastoidectomy group, although evaluating both the large (completely exenterated mastoid)- and small cavity techniques, the focus was on the latter. With this technique, disease is surgically approached from its site of origin, and followed into the attic and mastoid. The resultant defect in the medial canal wall and mastoid is kept as small as possible, to avoid obliteration and the morbidity of an unnecessarily large cavity. Dry ears were achieved in 93% of patients. In cases where the TM was grafted, an intact tympanic membrane was achieved in 85% of patients. Significant hearing improvement (>10dB in two consecutive frequencies) was achieved in 33% of patients who had the tympanic membrane grafted to an intact stapes suprastructure (Type 3 tympanoplasty with or without a cartilage columella). These results compared favourably to the large cavity CWD technique in this series where obliteration and middle ear grafting were not performed on a regular basis. In this group, only 16% of patients had an intact tympanic membrane post-operatively, and 63% of ears were dry at latest follow up. Although statistical analysis did not show one technique to be superior to the other in achieving a dry ear post-operatively (p= 0,39), the results with the small cavity technique were very encouraging. Hearing improvement in both groups were variable and hearing preservation rather than augmentation was achieved in most. The lack of hearing improvement may not only have been related to the extensive disease encountered (80% extending beyond attic, 50 % stapes suprastructure erosion), but also to inadequate and infrequent reconstruction of the middle ear.
Keywords: Otitis Media